CAN A NON-MEMBER SPOUSE PROTECT HIS OR HER INTEREST IN THE MEMBER SPOUSE’S ACCRUED PENSION BENEFITS BEFORE DIVORCE? - MC Marumoagae (Obiter, 2016)
A court hearing a divorce matter is empowered by relevant provisions of the Divorce Act to order that a portion of a member spouse’s pension interest be assigned to his or her former spouse, which amount should be paid by the member’s pension fund when it “accrues”. In order to ensure that a non-member’s spouse does not wait for a long period after the divorce to be paid his or her share of the member’s pension interest, the clean break principle has been introduced to enable him or her to immediately claim his or her share of the member spouse’s pension benefits on the date of divorce. However, when one spouse has been accorded his or her pension benefits during the subsistence of the marriage, there is no legislative provision which forces such a spouse to share such benefits with his or her non-member spouse. But the same spouse can claim against the pension interest of the other spouse when parties divorce. This note argues that there is a need for a legislative provision which would empower non-member spouses married in community of property to claim part of the pension benefits of their member spouses when they accrue during the subsistence of the marriage.